1995
DOI: 10.1111/j.1540-8159.1995.tb06966.x
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Index at Three Atrial Sites in Patients with Paroxysmal Atrial Fibrillation

Abstract: The purpose of this study was to evaluate the wavelength index (WLI) at three atrial sites in a group of 23 patients with recurrent episodes of lone paroxysmal atrial fibrillation (LPAF) and a control group (n = 20). All patients underwent programmed atrial stimulation (paced cycle length = 600 ms) at high, medium, and low lateral right atrial wall. P wave duration, sinus cycle length, and corrected sinus node recovery time were not significantly different between the two study groups. WLI was calculated accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…Some previous studies found that a shorter wavelength index indicated greater vulnerability to atrial fibrillation. 10,14,16) In this study, the wavelength index was shorter in patients with inducible atrial fibrillation than in those without inducible atrial fibrillation, which is consistent with these previous reports. However, we found no correlation between the wavelength index and age, which is the first time this finding has been described.…”
Section: Patient Characteristicssupporting
confidence: 82%
See 4 more Smart Citations
“…Some previous studies found that a shorter wavelength index indicated greater vulnerability to atrial fibrillation. 10,14,16) In this study, the wavelength index was shorter in patients with inducible atrial fibrillation than in those without inducible atrial fibrillation, which is consistent with these previous reports. However, we found no correlation between the wavelength index and age, which is the first time this finding has been described.…”
Section: Patient Characteristicssupporting
confidence: 82%
“…Although the effects of the underlying diseases on atrial vulnerability might not be negligible, this is a limitation common to many studies. 7,14,16) In this study, we found no difference with respect to age between patients with and without inducible atrial fibrillation, which is not concordant with previous reports. 1,2) The reason for this discrepancy might be due to the underlying arrhythmias.…”
Section: Patient Characteristicssupporting
confidence: 37%
See 3 more Smart Citations